PEMBEBASAN PEREMPUAN DARI DOMINASI LOGIKA MASKULIN DALAM PERSPEKTIF LUCE IRIGARAY - Batlayeri, Willem (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2021)
This paper aims to explore Luce Irigaray's thoughts regarding the problem of masculine domination. In the process of studying the thought of Irigaray, the method used is the method of literature(LibraryResearch), which is a series of activities that are pleasing to the method of data collection library, read, record and process the research data. With this method, it will be shown how Iragaray's criticism is aimed at destroying the hegemony of the tradition of patriarchal thought. For Irigray, patriarchal discourse has constructed women as inferior, lower under the superiority of men. Therefore, by emphasizing the subjectivity of women, the logic of masculine domination can be understood, especially when placed in a mimetic way of thinking. Mimeticism is used by Irigaray to distinguish the thought traditions of women and men in constructing knowledge, even language is influenced by patriarchal discourse. Keywords: Masculine, superiority, subjectivity